Konsep Tarbiyah Menurut Hasan Al-Banna dan Abul A’la Maududi:Sebuah Kajian Literatur - Mutalib, Wahyudi (Educational Research Center, 2025)
The study of contemporary Islamic educational thought highlights the urgent need to build a conceptual bridge between the classical Islamic educational tradition and modern Western educational philosophy. This article aims to provide a comprehensive examination of the concept of tarbiyah as articulated by Hasan Al-Banna and Abul A‘la Maududi—two influential twentieth-century thinkers who made significant contributions to the formation of modern Islamic educational paradigms. The research employs a library research method with a content analysis approach, focusing on the primary works of both figures as well as relevant secondary sources. The analysis centers on identifying similarities, differences, and potential avenues for conceptual dialogue between their notions of tarbiyah and the framework of modern Western education. The findings reveal that Al-Banna emphasizes the spiritual, moral, and social-practical dimensions in shaping the complete Muslim individual, while Maududi highlights ideological and political aspects as the foundation for establishing an Islamic social order. Despite their differing orientations, both share a common goal—forming the insan kamil (the perfect human being) who is faithful, knowledgeable, and virtuous. Theoretically, this study contributes to the development of a conceptual synthesis between Islamic and Western education by integrating spiritual values with modern rationality. Practically, the findings serve as a foundation for educators and policymakers in designing holistic Islamic education curricula that accommodate the spiritual, intellectual, and social needs of contemporary Muslim societies. Thus, this research underscores the enduring relevance and vitality of Al-Banna’s and Maududi’s ideas in bridging the East–West dichotomy within modern educational discourse.